Understanding the Socio-environmental Consequences of Rohingya Refugee: A Study on the Perceptions of Host Community - Eyemoon, Eashrat Jahan; Zaman, Md Ohidur (Social Science Review, 2023)
Rohingya refugees came into a massive influx in Bangladesh in 2017 and overwhelmed the camp areas with myriads of problems especially degrading environment and creating social chaos. This study seeks to understand the perception of local people about Rohingya refugees regarding the impacts of refugees on the host community from both environmental and social perspectives. The study finds that in the initial period of the refugee influx, local people showed their sympathy and provided support to help these forced migrants. However, the perception of local people started to change over time as they believed that because of the massive influx of refugees, the host environment lost a thousand acres of forest, more than half of the total hill lands, and vast biodiversity. Moreover, due to the establishment of refugee camps, the host communities face several social problems like theft, robbery, hijacking, teasing, violence, smuggling, etc. The long presence of refugees in an area with scarce resources brings social tensions and competition that may turn into social conflict if there is a lack of proper surveillance and policies from respective authorities. Social Science Review, Vol. 39(3), Dec 2022 Page 1-16